2016
DOI: 10.1515/eurodl-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Associated with MOOC Engagement, Retention and the Wider Benefits for Learners

Abstract: Massive Open Online Courses (MOOCs) have and continue to change the way in which nontraditional learners' access education. Although the free element of these has been linked to low completion rates due to no invested interest, the MOOC platform enables innovative technologies and practices to be trialled. Therefore, rather than attributing varied intentions of learners for high drop-out rates, it is suggested that an increase in completion can be achieved through more focussed pedagogical practices. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 8 publications
3
18
0
2
Order By: Relevance
“…Overall, the findings from this study are consistent with the previous literature focussing on the need to understand attrition factors and motivational transition across MOOCs (Xu & Yang, 2016). Accordingly, it has also been suggested that pedagogical models should consider the technology practices involved (e.g., digital skills) to engage participants continuously to increase retention (Petronzi & Hadi, 2016). The combination of factors evaluated in this study (motivation, knowledge, satisfaction level) follows suggestions about not relying on behavioral aspects exclusively, but instead, including cognitive elements, as both aspects are related to MOOC engagement, and both increase the probability of completing a course (Li & Baker, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the findings from this study are consistent with the previous literature focussing on the need to understand attrition factors and motivational transition across MOOCs (Xu & Yang, 2016). Accordingly, it has also been suggested that pedagogical models should consider the technology practices involved (e.g., digital skills) to engage participants continuously to increase retention (Petronzi & Hadi, 2016). The combination of factors evaluated in this study (motivation, knowledge, satisfaction level) follows suggestions about not relying on behavioral aspects exclusively, but instead, including cognitive elements, as both aspects are related to MOOC engagement, and both increase the probability of completing a course (Li & Baker, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Li and Baker (2018) found heterogeneity in behavioral patterns among learners that is expression of different levels of engagement, and different reasons why participants decide to engage (see also Walji, Deacon, Small, & Czerniewicz, 2016;Williams, Stafford, Corliss, & Reilly, 2018;Zhang, Cesar Bonafini, Lockee, Jablokow, & Hu, 2019). In sum, they conclude that in MOOCs the existence of self-defined learning pathways generates the need to apply different measures to discern the way learners are taking advantage of the content of the courses (see also Petronzi & Hadi, 2016;Reilly, Williams, Stafford, Corliss, Walkow, & Kidwell, 2016;Shapiro, Lee, C. H., Wyman Roth, Li, Çetinkaya-Rundel, & Canelas, 2017;Tseng, Tsao, Yu, Chan, & Lai, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Again, this demonstrates the range of considerations for HEIs during the COVID-19 pandemic and beyond. Indeed, previous research (Petronzi & Hadi, 2016) that explored feedback from online learners showed the importance of academic involvement and peer interaction via discussion boards that offered learners a platform to share experiences and to gain support. This is deliverable provision but can also be expanded upon using live collaborative digital solutions e.g.…”
Section: Social Learning and Motivation Through A Blended Approachmentioning
confidence: 99%
“…Group work challenges learners by encountering divergent opinions, learning through peer modelling, risk-taking and engaging in collaborative problem-solving Aubrey & Riley, 2019;Dennick, 2012;Kolb & Kolb, 2005). It should be noted, however, that collaborative/group work is not limited to face-to-face sessions (Petronzi & Hadi, 2016). While we place emphasis on the campus setting for peer-to-peer engagement, the use of collaborative digital software, including group discussion boards, can replicate group work through producing a dialogic environment (Gibson, 2012).…”
Section: Social Learning and Motivation Through A Blended Approachmentioning
confidence: 99%